Inferences in text processing - Rickheit, Gert; Strohner, Hans (Advances in psychology (Amsterdam, Netherlands), 1985)
This volume critically evaluates the present state of research in the domain of inferences in text processing and indicates new areas of research. The book is structured around the following theoretical aspects: - The representational aspect is concerned with the cognitive structure produced by the processed text, e.g. the social, spatial, and motor characteristics of world knowledge. - The procedural aspect investigates the time relationships on forming inferences, e.g. the point of time at which referential relations are constructed. - The contextual aspect reflects the dependence of inferences on the communicative embedding of text processing, e.g. on factors of modality and instruction.